The second epistle general of Peter and the general epistle of Jude an introduction and commentary - Green, Michael, 1930- (Leicester, UK IVP, 1987)
Includes bibliographical references.
Keywords: Bible. N.T. Peter, 2nd -- commentaries; Bible. N.T. Jude -- commentaries